PERSEPSI NASABAH TERHADAP PEMBIAYAAN MURABAHAH DALAM PENGEMBANGAN UMKM (STUDI KASUS PADA BANK BSI MATARAM HASANUDDIN) - Sri Hadiatini; Herawati Khotmi; Khairul Hadi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study attempted to examine the effect of perceived demand pressure, ease of service, reputation footprint, and perceived level of excellence on cost-plus financing and the influence of perceived demand pressure, ease of service, reputation footprint, and level of product advantages together against the financing. Thus, this quantitative research involved 371 customers who transacted cost-plus financing. The slovin formula was applied as sampling technique with a total sample of 79. Moreover, the analytical technique employed in this study was starting from the validity test, reliability test, classical assumption test, hypothesis testing with simple regression, and multiple regression with SPSS data processing. Therefore, the findings indicated that the perception of the need urgency for ease of service, the reputation trace, and the perception of the level of product excellence affected the cost-plus financing. Meanwhile, the ease of service and the level of product excellence perceptions impacted cost-plus financing. In contrast, the perception of demand and reputation footprint does not affect the financing.